Development of distributed subject-oriented applications for cloud computing through the integration of conceptual and modular programming - Feoktistov, A. G.; Kostromin, R. O.; Sidorov, I. A.; Gorsky, S. A. (2018 41st International Convention on Information and Communication Technology, Electronics and Microelectronics (MIPRO), 2018)
The paper addresses the relevant problem related to the development of distributed object-oriented applications to solve large-scale scientific and applied problems in a public access computer center. The center includes dedicated resource for cloud computing (private cloud) and non-dedicated resources for traditional distributed computing. Applications generate flows of computational jobs. We propose a new approach to the development of applications. It based on the integration of conceptual and modular programming. We also create two toolkits to support proposed approach and develop applications. Applications software is based on the use of knowledge embedded in the conceptual model of the environment. It describes the parameters of subject domains, operations over parameter field, software modules (applied software) that implement operations, computational nodes, communication channels and other objects of both the subject domains and environment, including the relationships between objects. In comparison to the known tools, used for the development and execution of distributed applications in the current practice, the created toolkits provide executing application jobs in the integrated environment of virtual machines that include both the dedicated and non-dedicated resources of the center. Experiments of solving large-scale practical problems of optimization of multiextremal functions and warehouse logistics show the effectiveness of the developed applications.